Anterior and Posterior Cruciate Ligaments Mechanoreceptors: A Review of Basic Science - Konstantinos Banios; Vasileios Raoulis; Apostolos Fyllos; Dimitrios Chytas; Vasileios Mitrousias; Aristeidis Zibis (Diagnostics, 2022)
Proprioception is a specialized sensory modality encompassing the movement of the joint and its position in space, and it involves the conversion of mechanical deformation of tissues into neural signals. Mechanoreceptors are specialized nerve structures able to transmit mechanical deformation through electrical signals to dorsal root ganglion sensory neurons and are abundant in the muscles, tendons and ligaments of the knee joint. They are believed to play an important role in knee proprioception and dynamic knee stability. Proprioception should always be taken into consideration for successful reconstruction of the cruciate-deficient knee and for pain and function management in the arthritic knee. Advances in histological methods of detection are numerous and continue to highlight the presence and role of mechanoreceptors after ligament reconstruction, depending on choice of graft. In this review, we present the current knowledge of anterior and posterior cruciate ligaments and grafts mechanoreceptors, and their role in proprioception of knee joint, focusing on each type of mechanoreceptors.